The power relations that permeate the Irrigated Perimeter Várzeas de Sousa-PB (PIVAS) (Research, Society and Development, 2019)
This article aims to analyze the public policy of the creation of floodplains Irrigated Perimeter Várzeas de Sousa-PB (PIVAS) and power relations involving farmers and entrepreneurs. The waterbuck is located between the municipalities of Sousa and Aparecida, in the middle region of the Hinterland of the State of Paraiba, featuring as a major socio-economic importance of the project for the region, adopting the trend of new regional production areas, constituting an initiative of the State Government Paraíba in conjunction with the local political power in order to boost agricultural and agro-industrial activities in the State of the hinterland. The methodology was a bibliographical study based on literature on public policies, with qualitative and descriptive approach. From what has been reported it can be seen that the project would initially focused on business production was distributed among peasants who ended up adapting the idea of agribusiness imposed by the business model.